2005
DOI: 10.1080/13607860500131427
|View full text |Cite
|
Sign up to set email alerts
|

Functions of reminiscence and mental health in later life

Abstract: This study examines the extent to which various forms of reminiscence predict life satisfaction and psychiatric distress with and without control for the contribution of personality traits (n=420). Among older adults, reminiscences to revive old problems and to fill a void of stimulation were associated with lower life satisfaction and greater psychiatric distress. Reminiscence to maintain connection with a departed person also predicted psychiatric distress. In contrast, reminiscences for death preparation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
0
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 21 publications
6
132
0
10
Order By: Relevance
“…In a recent study using the RFS, it was found that higher levels of bitterness revival, boredom reduction, death preparation and total reminiscence correlated with higher levels of anxiety and that depression was correlated with bitterness revival (Cully et al, 2001). Cappeliez, O'Rourke and Chaudhury, (2005) found that boredom reduction and bitterness revival predicted lower life satisfaction, and death preparation predicted higher life satisfaction. These studies show that mere stimulation of reminiscence may not always enhance psychological well-being.…”
Section: Moderatorsmentioning
confidence: 99%
“…In a recent study using the RFS, it was found that higher levels of bitterness revival, boredom reduction, death preparation and total reminiscence correlated with higher levels of anxiety and that depression was correlated with bitterness revival (Cully et al, 2001). Cappeliez, O'Rourke and Chaudhury, (2005) found that boredom reduction and bitterness revival predicted lower life satisfaction, and death preparation predicted higher life satisfaction. These studies show that mere stimulation of reminiscence may not always enhance psychological well-being.…”
Section: Moderatorsmentioning
confidence: 99%
“…Wink and Schiff (2002) suggest that only 30-50% of the older adults go through a process of life-review. In addition it has been found that some reminiscence styles (boredom reduction and bitterness revival) correlate strongly with both psychological distress and neurotic personality traits (Cully et al 2001;Cappeliez et al 2005). Theoretically this would make persons with these reminiscence styles prime candidates for life-review interventions, but it is yet unclear to what extent negative reminiscence styles can indeed be changed.…”
Section: Discussionmentioning
confidence: 99%
“…Identity-forming reminiscence (similar to Integrative reminiscence or life-review) and problem-solving reminiscence (similar to instrumental reminiscence) have been found to correlate with successful aging (Wong and Watt 1991). Reminiscence for the sake of bitterness revival was found to correlate with higher levels of depression (Cully et al 2001;Cappeliez et al 2005). Therefore reminiscence as treatment of late-life depression should not only promote integrative reminiscence and problem-solving reminiscence but also reduce or transform bitterness-revival.…”
Section: Introductionmentioning
confidence: 99%
“…General strategies to minimise the negative impact that these changes might have on quality of life include the individual use of reminiscence 3,18 , dancing 19,20 , maintaining activity 21 , independence 3 , social relationships and affiliations 22,4,6 and engagement with family 23,24 , 'mainstream' society 25 and by going out 23 . When this was not possible, having established primary or secondary (cognitive adaptation) 5 control and influence over informal care 8 and/or external help and services 3,6,26 was seen as an important component of maintaining a good quality of life.…”
Section: Introductionmentioning
confidence: 99%